Development of School Reproductive Health Education Index Model (Indeks Pendidikan Kesehatan Reproduksi Sekolah / IPKPRS) (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
One of the important health issues to be on the agenda of health promotion in schools is reproductive health. The results of the Basic Health Research (Riskesdas) in 2018 showed that nationally as many as 65.2% of the population had less knowledge about HIV/AIDS. This indicates that Indonesia is faced with the problem of low reproductive health literacy of school residents. The RD design is used to develop the School Reproductive Health Education Index (IPKRS) instrument. RD is carried out in 3 stages, namely: 1) determination of IPKRS dimensions and parameters by the focus group discussion (FGD) method; 2) Preparation, consultation and revision of the IPKRS model through experts judgment by the Delphy method; 3) Testing the validity of IPKRS by experts. The results shows that there are 4 dimensions of IPKRS, namely 1) the knowledge of school residents; 2) curriculum; 3) infrastructure; 4) institutional. The four dimensions are described in 13 IPKRS parameters. The validity test results shows all IPKRS parameters proved to be valid (Aikenâ€™s coefficient V value for each item â‰¥ 0.92). The findings of the IPKRS model need to be followed up by implementing in schools within the framework of mapping the quality of school reproductive health education.